2006
DOI: 10.2174/187152006778699095
|View full text |Cite
|
Sign up to set email alerts
|

New Generation of Liposomal Drugs for Cancer

Abstract: This review is focused on liposomes as a delivery system for anticancer agents and more specifically on the advantages of using liposomes as drug nanocarrier in cancer chemotherapy. The main advantages of liposomal drugs over the non-encapsulated drugs include: (1) improved pharmacokinetics and drug release, (2) enhanced intracellular penetration, (3) tumor targeting and preventing adverse side effects and (4) ability to include several active ingredients in one complex liposomal drug delivery system (DDS). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(54 citation statements)
references
References 0 publications
3
50
0
1
Order By: Relevance
“…It is well known that liposomal drug formulations are more efficient in terms of their cellular internalization, specific activity, and adverse side effects when compared with free drugs (28,(37)(38)(39)(40)(41)(42)(43). Liposomes of different sizes and surface electric charges are currently being used for the liposomal drugs in terms of their successful intracellular uptake, organ retention, and treatment efficacy after administration via different routes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that liposomal drug formulations are more efficient in terms of their cellular internalization, specific activity, and adverse side effects when compared with free drugs (28,(37)(38)(39)(40)(41)(42)(43). Liposomes of different sizes and surface electric charges are currently being used for the liposomal drugs in terms of their successful intracellular uptake, organ retention, and treatment efficacy after administration via different routes.…”
Section: Discussionmentioning
confidence: 99%
“…Liposomes have been used successfully to deliver conventional drugs or new genetic drugs including plasmid DNA-containing therapeutic genes, antisense oligonucleotides (ASO), and small interfering RNA (siRNA) in preclinical models and clinical trials (24)(25)(26)(27)(28)(29)(30)(31)(32). The delivery of different types of payloads in turn requires different properties of carriers, including their surface charge.…”
Section: Introductionmentioning
confidence: 99%
“…SSL-DiR and iRGD-SSL-DiR exhibited similar size distribution (134.9 ± 9.66 nm and 131.6 ± 11.6 nm, respectively) and zeta potential (À2.46 ± 0.85 mV and À3.19 ± 0.30 mV, respectively). As shown in Figure 5A, though liposomal formulations significantly improved circulation profiles and had EPR effect owing to PEG modification (Minko et al, 2006), there was high accumulation in liver and spleen as shown in the ex vivo image ( Figure 5B), possibly because of the arrestment of DiR-loaded formulations by RES system (Schädlich et al, 2011;Xiang et al, 2011). However, superior distribution of liposomes, especially iRGD-SSL-DiR at 12-h post-injection, in tumors could still be observed.…”
Section: Cytotoxicity Assaymentioning
confidence: 96%
“…Packaging of chemotherapeutics within nanosized formulations like liposomes has been of considerable interest in the past few years (Crommelin & Storm 2003;Metselaar & Storm 2005;Minko et al 2006) and liposomes are considered to be one of the most successful DDS (Kaneda 2000); a number of liposome-based systems have been approved by the US Food and Drug Administration (FDA) for disease treatment in the clinic. Although due to their small size liposomes can enter the arterioles and epithelial fenestration, drug solubility is an important concern for liposome based DDS.…”
Section: Nanomaterials In Drug Deliverymentioning
confidence: 99%